The union makes life program in the context of social responsibility: the contributions of Sicredi Upper Uruguai - Tres, Rafael; Bonzanini, Osmar Antonio; Olesiak, Estevo Mateus (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
This paper aims to present the importance of social projects nowadays, with this line, cooperative system arises. This systemis very important when it comes to achieving a certain result because in the cooperatives all those involved work together in pursuit of a common goal. The Credit Cooperative of Free Admission Associates –Sicredi, realized then, such need of being created a program which has as itspurpose to work cooperation since the beginning of people's lives, as they learn easier when they are younger, because these people do not have a fixed idea about all the issues that surround them, it was then that came the program The Union Makes Life. This program is very important for personal growth of all involved, it aligns to a style of cooperative work, where several people perform the same activity seeking to achieve a common result for all of them and give them the opportunity of a better qualityof life. The Program The Union Makes Life operates in the municipalities where Sicredi is inserted, in partnership with the city itself, with both parties making investments of equal value to fund projects and activities related to the program.